Isolation of Cellulolytic Lactic-Acid Bacteria from Mentok (Anas moschata) Gastro-Intestinal Tract - H. Herdian; L. Istiqomah; E. Damayanti; A. E. Suryani; A. S. Anggraeni; N. Rosyada; A. Susilowati (Tropical Animal Science Journal, 2018)
Mentok, a local Indonesian name’s of muscovy duck (Anas moschata), has been known as a duck with the capability to consume poor quality feed, high with non-starch carbohydrate (NSP) content. This capacity occurs because of the presence of microbial fermentation activity in the gastro intestinal tract (GIT) of mentok. However, the information about the identification and characterization of the cellulolytic microbes involved is limited. This study was expected to provide scientific contributions about gastrointestinal microbes, especially Lactic Acid Bacteria (LAB), with cellulolytic activities. The experiment was conducted to select LAB with cellulolytic activity from the GIT of mentok. Twenty six of selected LABs were isolated from the duodenum, cecum, and colon regions after microbiological characterization, i.e., morphology, catalase test, gas production, Gram staining, and motility test. Characterization for cellulolytic activity was analyzed by measuring the clearing zone on Carboxymethylcellulose (CMC) media, cell growth analysis on 1% CMC as a carbon source, and CMCase value. Pediococcus acidilactici MK 20 isolate from colon region was selected LAB with the highest cellulolytic activity with the clearing zone diameter, and the CMCase value of 2.33 mm and 0.0153 U/mL, respectively. Molecular identification using 16S rRNA gene sequences analysis revealed that P. acidilactici MK 20 isolate has 99% similarity with P. acidilactici strain ZW001. It was concluded that P. acidilactici MK 20 isolated from the colon part of the  gastrointestinal tract of mentok, the Indonesian muscovy duck (A. moschata) had cellulolytic activity.